Bridging the Gap between Neuroscience and Education: What are Teachers’ Perceptions of Applying “Neuropedagogy” to High School Classrooms? - Rashwan, Hanan (AUC Knowledge Fountain, 2024)
Teachers can use neurobiological explanations to evaluate students' behavior and performance and create more supportive learning settings in their school environment. There is a growing interest among educators regarding the potential benefits of incorporating neuroscience into teaching practices. However, there is a lack of comprehensive understanding of how to effectively integrate cognitive neuroscience into teacher education programs to maximize its impact on student learning and teacher development. This study focuses on understanding teachers' views on the integration of neuroscience principles in educational settings by utilizing a questionnaire and interviews to gather data from participating teachers. The findings reveal that the teachers hold a positive perception of the connection between neuroscience and education. The teachers also emphasize the value of studying the brain and gaining insights into cognitive functions such as attention, memory, and motivation. The teachers' perspectives highlight the importance of integrating neuroscience principles into educational practices to create more effective and personalized learning experiences. This research underscores the transformative potential of integrating neuroscience and education. The positive perceptions of teachers resonate with the need for informed and dynamic teaching methodologies that align with the intricacies of the human mind. By embracing neuroscience principles, educators can unlock new frontiers in education, empowering both teachers and students to reach unprecedented levels of knowledge and achievement.